Chronicle of a Pigmented Superficial Basal Cell Carcinoma. (8th July 2012) - Caucanas, Marie; Piérard-Franchimont, Claudine; Piérard, Gérald E.
Abstract : Dermoscopic patterns of basal cell carcinoma (BCC) are well defined, but the dynamics of dermoscopic changes in time were apparently never described so far. In this paper, prominent changes were observed over a 8-week period, allowing to establish a close connection between spoke wheel areas and maple leaf-like aspects, through progressive thickening of the former ones. A chronobiological phenomenon ruling synchronous apoptosis in some of the most superficial BCC nests is suggested, leading to a wax and wane process of millimetric crusts, taking part in the spontaneous BCC regression/progression process.